Hot new lifestyle hotel brands: best practices - Rosen, Joel (Henry Stewart Talks, 2009)
What is a lifestyle brand?, Principles of lifestyle hotel brands, Four best practices, Selected major hotel brands, In-depth research, Clear vision, Product differentiation, Implementation